1976
DOI: 10.1620/tjem.120.251
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ligation of Vas Deferens, Corpus Epididymidis and Vasa Efferentia on the Testicular Function in Rats

Abstract: Med., 1976, 120 (3), 251-257-The effects of ligation of the vas deferens, the corpus epididymidis and the vasa efferentia on the testicular function were studied in sexually mature rats. The significant decrease in the testicular weight was observed after ligation of the corpus epididymidis and the vasa efferentia. However, neither the weight of the ventral prostate and of the seminal vesicle, nor the plasma testosterone level showed significant changes. The results suggest that the ligation at the three locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In contrast to the disagreement resulting from earlier reports, recent experiments support the view that testicular atrophy does not occur in rats that have been surgically vasectomized for less than 1 year (Heller & Rothchild, 1974;McGlynn & Erpino, 1974;Neaves, 1974;Hernández-Jáuregui & Olivera, 1975;Howards, Jessee & Johnson, 1975;Mock, Kamel, Wright &Frankel, 1975;Neaves, 1975b;Voglmayr, 1975;Kuwahara, 1976;Lohiya, Dixit & Arya, 1976; Reinke & Stohs, 1977). These studies were confined to outbred rats, primarily to those of the Sprague-Dawley strain.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast to the disagreement resulting from earlier reports, recent experiments support the view that testicular atrophy does not occur in rats that have been surgically vasectomized for less than 1 year (Heller & Rothchild, 1974;McGlynn & Erpino, 1974;Neaves, 1974;Hernández-Jáuregui & Olivera, 1975;Howards, Jessee & Johnson, 1975;Mock, Kamel, Wright &Frankel, 1975;Neaves, 1975b;Voglmayr, 1975;Kuwahara, 1976;Lohiya, Dixit & Arya, 1976; Reinke & Stohs, 1977). These studies were confined to outbred rats, primarily to those of the Sprague-Dawley strain.…”
Section: Introductionmentioning
confidence: 76%
“…The apparent normality of testosterone levels after vasectomy in rats (Mock et al, 1975;Neaves, 1975b;Voglmayr, 1975 ;Kuwahara, 1976) has not encouraged pursuit of hormonal mechanisms of spermatogenic impairment, and more study has been devoted to sperm-specific autoimmunity because of its evident involvement in post-vasectomy hypospermatogenesis in guinea-pigs (Alexander, 1973) and rabbits (Bigazzi et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the ductuli efferentes, unless attenuated within a short period of time, will initiate extensive degeneration of the seminiferous epithelium of the testis that may persist for long periods of time and lead to irreversible infertility. This can occur in many experimental and clinical conditions, including 1) ligation (Cunningham, 1928;Harrison, 1953;Kuwahara, 1976;Smith, 1962;Van Wagenen, 1925), 2) ablation of the epididymal blood vessels (MacMillan, 1953),3) congenital agenesis (Dubin and Amelar, 1971;Makler and Hampel, 1975) and maldevelopment (Ashdown, 1985;Gustafsson and Galloway, 1988;Shafik and El-Sibaei, 1991), 4) congenital occlusions (Ikadai et al, 1987), 5) varicocele in humans (Nistal et al, 1984(Nistal et al, , 1987, 6) vasectomy (Tung and Alexander, 19801, 7) vitamin E deficiency (Mason and Shaver, 19521, 8) Young's syndrome (Hendry et al, 19901, 9) granuloma, sperm stasis, and cysts (Blom and Christensen, 1960;Hamm et al, 1988;Hemeida and McEntee, 19841, and 10) chemical toxicoses, ethylene dimethane sulfonate and a-chlorhydrin Jackson, 1972, 1973), benzimidazole carbamate (Hess et al, 1991;Nakai et al, 1992,19931, cadmium (Mason andYoung, 1967;Nagy, 19851, and dinitrobenzene (Linder et al, 1988a).…”
Section: Functional Disordersmentioning
confidence: 99%
“…There have been some studies on experimental spermatoceles obtained by surgical ligation of the excurrent duct ( Smith, 1961; Kuwahara & Frick, 1975; Kuwahara, 1976). The studies demonstrated that vasectomy induces spermatoceles accompanied by spermatic granulomas at the ligated site.…”
Section: Discussionmentioning
confidence: 99%
“…The studies demonstrated that vasectomy induces spermatoceles accompanied by spermatic granulomas at the ligated site. However, it was found that complete ligation of the efferent ducts in rats did not induce the formation of spermatoceles ( Smith, 1961; Kuwahara & Frick, 1975; Kuwahara, 1976). It was only observed that the seminiferous tubules first became dilated, followed by severe degeneration and atrophy of the seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 99%